Has Japan been following Modern Money Theory without recognizing it? No! and yes - Larry Randall Wray; Yeva Nersisyan (Levy Economics Institute of Bard College, 2021)
Modern Money Theory (MMT) economists have used Japan as an example of a country that demonstrates that high deficits and debt do not lead to insolvency, high interest rates, or inflation. MMT insists that governments that issue their own sovereign currency cannot be forced into insolvency, that they can make all payments as they come due, and that they do not really spend tax revenue or borrow in their own currency-with Japan serving as an example of a country that does not face financial budget constraints as normally defined. In this paper we evaluate whether Japan is the poster child of MMT and argue that policy-wise Japan is not following MMT recommendations; in fact, it is generally adopting policies that are precisely the opposite of those proposed by MMT, consistently adopting the path of stop-go fiscal measures and engaging in inadequate and temporary fiscal stimuli in the face of recessions, followed by austerity whenever the economy has seemed to recover.
Keywords: E12; E32; E42; E58; H62; H63; 330; Modern Money Theory; Budget Deficits; Sovereign Debt; Japanese Government Debt; MMT Policy